Produksi dan Kualitas Buah Stroberi pada Beberapa Sistem Irigasi - Slamet Susanto; Bhayu Hartanti; Nurul Khumaida (Indonesian Society for Horticulture / Department of Agronomy and Horticulture, 2010)
ABSTRACTThe objectives of this research was to study the fruit production and quality of strawberry grown under different irrigation system. The trial was arranged in a completely randomized design. Four irrigation systems were examined: drip irrigation applied daily, drip irrigation applied every 2 days, manual irrigation applied daily and manual irrigation applied every 2 days . The result showed that the treatments gave significant effects on vegetative growth. Plants irrigated daily produced more runn er than those irrigated every 2 days. Plants irrigated manually every 2 days lowered flower production. The drip irrigation applied daily gave the highest response on growth and yield without any difference on fruit quality. The system could be considered for hydroponic strawberry production.Key words: strawberry, irrigation, fruit production, fruit quality